Seamless Integration of Heterogeneous Components in a Distributed Simulation Infrastructure - de Mello, Braulio Adriano (2009)
The utilization of simulation in the design of systems combining different parts (heterogeneous systems) contributes with the validation, verification, and observation of the behavior of these parts (individually) and of the cooperation between them. The differences between the parts (elements) that compose the model of representation (of a system) make these tasks more complex due to three main aspects: the reuse, the preservation of elements and the interface compatibility. The reuse of existing elements can facilitate and accelerate the construction of new models or the modification of existing ones. Nevertheless, the probability of having a heterogeneous model increases since the elements can be developed under conditions that vary in terms of description language, interface configuration, operational environment, and others. Thus, it is highly likely the need of making an element have alterations or adaptations that can jeopardize the preservation of its original characteristics or even interfere in intellectual properties issues, in order to be reused. The compatibility between interfaces of different elements is neither guaranteed. Regarding these challenges, this paper presents DCB (Distributed Co-simulation Backbone), an infrastructure for distributed simulation that offers mechanisms for preserving elements of the model from interface adaptations and for implementing data translation and communication and synchronization, all of them necessary for the execution of a heterogeneous model. By implementing these aspects in a backbone that is independent from the elements, DCB can preserve their integrity without loosing the capability of adaptation of heterogeneous elements so as to be able to cooperate correctly when integrated into the same simulation model. DCB also permits the execution of a simulation with elements distributed in different nodes.